The impact of high temperature on mechanical properties and behaviors of sandstone - Jin, Juan; Liu, Jiandong; Chen, Weixi; Li, Guoping; Cheng, Wei; Zhang, Xiaowen; Luo, Yifan (Frontiers in Earth Science, 2024)
The impact of high temperature environments on the physical and mechanical properties of rocks is a significant factor to consider. The investigation into the impact of elevated temperatures on the physical and mechanical characteristics of rocks holds great importance in the advancement and exploitation of deep-seated mineral reserves, as well as in ensuring the safety and stability of subterranean engineering projects. This study utilizes the state-of-the-art GCTS Mechanical Loading Test System to conduct uniaxial and triaxial compression tests on sandstone after thermal treatment from 25 to 650 °C. In addition, XRD, SEM and nuclear magnetic resonance experiments were carried out on the sandstone after thermal treatment. The aim of the experiments is to provide a quantitative characterization of mechanical properties and behaviors of the rock samples. The results show that the mass, density, and wave velocity of sandstone decrease with increasing temperature, while volume and porosity increase. The mass, volume, and rate of density change of sandstone exhibit a significant increase when subjected to temperatures above 500°C. The uniaxial compressive strength and elastic modulus exhibit an initial increase followed by a subsequent decrease as the temperature rises, with 300℃ serving as the critical turning point. The axial peak strain and Poisson's ratio increase with increasing temperature. The cohesion decreases with increasing temperature, while the internal friction angle increases. Additionally, it is observed that the rate of change for both properties exhibits an increase beyond the temperature threshold of 400℃.